Prospect use of Phaleria macrocarpa to prevent motile aeromonad septicaemia disease in Patin Catfish Pangasianodon hypophthalmus - Wahjuningrum, D.; Angka, S.L.; Lesmanawati, W.; Sa’diyah, .; Yuhana, M. (Indonesian Society of Scientific Aquaculture (ISSA), 2007)
Motile Aeromonad Septicaemia (MAS) disease is one of bacterial disease frequently infecting freshwater fishes including patin catfish Pangasianodon hypophthalmus. This study was performed to determine antimicrobial of Phaleria macrocarpa (PM) and its potency against MAS disease caused by Aeromonas hydrophila. The in vitro susceptibility test was performed by pour plate methods at the dosages of 2, 4, 6, 8, and 10 g/l PM. At the in vivo test, fish were fed with the addition of PM into the diet at a dosage of 6, 12, and 18 g/l and 0 g/l as a control for 8 days. At ninth day, fish were infected with A.hydrophila. For seven days after infection the clinical signs and blood pictures were observed. The in vitro test indicated that PM had an antibacterial effect to A.hydrophila at the dosage of 6 g/l. Addition of PM in the diet for 8 days increased haemoglobine. The results showed that lowest clinical sign and smallest number of in fected fish was found at dosage of 12 g/l PM. PM can be used as a preventive method for MAS. Keywords: Phaleria macrocarpa, antibacterial,